2016
DOI: 10.1007/s00227-016-2892-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dietary shift in jellyfish revealed by stable isotope analysis

Abstract: A temporal change in the stable isotope (SI) composition of jellyfish in the Kiel Fjord, Western Baltic Sea, was documented by analyzing δ13C, δ15N and δ34S of bell tissue of Aurelia aurita and Cyanea capillata in the period between June and October 2011. A strong and significant temporal change in all SI values of A. aurita was found, including an increase of ~3 ‰ in δ13C, a decrease of ~4 ‰ in δ15N and sharp decline of ~7 ‰ in δ34S. While knowledge gaps in jellyfish isotope ecology, in particular the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Recently, Javidpour et al . 33 also suggested a temporal dietary shift from mesozooplankton to microplankton and re-suspended organic matter from the benthos for A . aurita from the Kiel Fjord (Baltic Sea).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, Javidpour et al . 33 also suggested a temporal dietary shift from mesozooplankton to microplankton and re-suspended organic matter from the benthos for A . aurita from the Kiel Fjord (Baltic Sea).…”
Section: Discussionmentioning
confidence: 96%
“…Comparison of stomach contents and zooplankton composition indicate that this jellyfish is a generalist predator, with a clear seasonal variation in its diet 27 , 29 . The seasonal changes in diet may lead to seasonal changes in the composition of FAs and, as for Aurelia aurita in the North Sea, to the temporal variability in jellyfish δ 15 N and δ 13 C SI signatures 33 . Other factors like physiology, changes in behavior, investment in reproductive output also could affect FAs and SIs 34 .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the assumption that jellyfish feed on mesozooplankton and ichthyoplankton is probably related with the essentially arbitrary use of 60–100 µm sieves to concentrate the samples for gut content analysis. In fact, when alternative methods like grazing experiments, microvideographic techniques, stable isotopes and fatty acid tracers are used it becomes apparent that jellyfish can also feed on microzooplankton ( Sullivan & Gifford, 2004 ; Colin et al, 2005 ), demersal zooplankton ( Pitt et al, 2008 ) and resuspended organic matter ( Javidpour et al, 2016 ). Therefore, our results should be regarded as a partial depiction of the diet composition of S. meleagris .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding scyphozoan jellyfish, two emerging issues are challenging the predominant view of competitive trophic interactions between planktivorous fishes and jellyfish. First, recent methodological approaches have shown that scyphozoans use unsuspected food sources, including benthic organisms ( Pitt et al, 2008 ; Ceh et al, 2015 ), microplankton and resuspended organic matter ( Javidpour et al, 2016 ). These food sources have been traditionally overlooked, because most studies on feeding ecology use gut content analysis that focuses on mesozooplankton and ichthyoplankton, presumably because they are more visible and retained in the gut for longer than other type of food ( Pitt, Connolly & Meziane, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…appear to be supported by field data (Frost et al 2012), but their application has resulted in apparently unrealistic trophic-level assignments (Fleming et al 2015, Nagata et al 2015. Hence, the resulting definitions of dietary composition and trophic niche remain uncertain (Nagata et al 2015, Javidpour et al 2016.…”
Section: Introductionmentioning
confidence: 99%